Determinants of Audit Fee - Evidence from Indian Companies - Ramesh, Latha; Kamath, Rajashree (Indian Journal of Finance, 2021)
Several studies have examined the factors influencing audit fees across the world, especially on the possible conflict of interest of auditor and client that may be affecting the quality of audit. The paper is about the trend in audit fee in the Indian setting, with the backdrop of two regulatory changes: mandatory auditor rotation and the implementation of Ind AS, the converged version of IFRS. Examining the determinants of audit fees, the paper categorized the explanatory variables into three attributes; auditee (size, risk, and complexity), auditor (auditor size, tenure, joint audit, and auditor rotation), and regulatory (mandatory auditor rotation and IFRS). The sample consisted of all non-financial companies listed on the National Stock Exchange for a period of 10 years from 2009 – 2018 resulting in 12,419 firm years. The paper deployed panel data regression with fixed effects with audit fee as the dependent variable. The key findings suggested that audit fee was positively associated with the size of the auditor and the auditee and the ratio of accounts receivable. The paper also indicated that with the tenure of the auditor, the fee tended to increase, and auditor rotation had a significant impact on the auditor's fee. The findings of the study will help the policymakers on the regulation around auditor engagements.